Heat-Conduction-Type and Keyhole-Type Laser Welding of Ti–Ni Shape-Memory Alloys Processed by Spark-Plasma Sintering - Bahador, Abdollah; Hamzah, Esah; Kondoh, Katsuyoshi; Tsutsumi, Seiichiro; Umeda, Junko; Abu Bakar, Tuty Asma; Yusof, Farazila (Nihon Kinzoku Gakkai, 2018)
High-brightness and high-power laser welding with different welding speeds and laser powers was applied to join Ti51 at%Ni shape-memory alloy, which was fabricated from the elemental pure Ti and pure Ni powders by spark-plasma sintering. Dendritic microstructures were observed in all the welds except the heat-conduction-type weld with the minimum welding parameters. In addition, the weld seam consisted of equiaxial grains surrounded by a narrow dendritic region. Based on the micro-X-ray diffraction pattern, in the keyhole-type welding, the martensite phase declined on increasing laser power and welding speed. Abnormal peak intensities were detected for (211) in the heat-conduction weld and (200) in the keyhole weld. Differential scanning calorimetry results revealed that phase transformation peaks of the conduction-type weld seam were similar to the base metal of Ti51 at%Ni SMA, whereas the corresponding peaks of the phase transformation in the other weld seams shifted towards lower temperatures due to Ni depletion in the matrix, grain coarsening and residual stress. Therefore, the findings suggest that heat-conduction-type can be a promising method for surface treatment of TiNi SMAs with minimum effect on the microstructure and shape memory properties.